STATISTICAL OPTIMIZATION OF AMYLASE PRODUCTION FROM ASPERGILLUS FLAVUS USING POD BIOMASS OF PITHECELLOBIUM DULCE AS SUBSTRATE. - SARITA SHEORAN,; RAJESH DHANKHAR, (International Journal of Pharma and Bio Sciences, 2016)
Microorganisms are extremely good with an amazing array of valuable products. But they usually produce them only in amounts that they need for their own benefit; thus, they tend not to overproduce their metabolites. Therefore, attempts have been made to specify the conditions to produce higher amylase on commercial scale. Present study mainly focused on optimization of amylase production in submerged fermentation by Aspergillus flavus. Three optimization parameters as pH, incubation time and temperature were treated as independent variables for the maximum production of amylase. These parameters were studied for the amylase production by using response surface methodology (RSM) based central composite design (CCD). The model equation provide a suitable model for the response surface for amylase production and from the optimal concentrations of the medium components, a model was predicted. The maximum amylase activity was predicted 22.89 IU/ml, when incubation time was 96 hrs, pH 6 and temperature 30°C.